2021
DOI: 10.1177/00238309211053033
|View full text |Cite
|
Sign up to set email alerts
|

Intraspeaker Priming across the New Zealand English Short Front Vowel Shift

Abstract: A growing body of research in psycholinguistics, corpus linguistics, and sociolinguistics shows that we have a strong tendency to repeat linguistic material that we have recently produced, seen, or heard. The present paper investigates whether priming effects manifest in continuous phonetic variation the way it has been reported in phonological, morphological, and syntactic variation. We analyzed nearly 60,000 tokens of vowels involved in the New Zealand English short front vowel shift (SFVS), a change in prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 69 publications
2
4
0
Order By: Relevance
“…In both cases we would characterize the duration of the repetitiveness effect as fairly long-lasting, extending over multiple intervening sentences. Generally speaking, the degree of durability here seems similar to previous results from other morphological and syntactic variables (Gries, 2005; Szmrecsanyi, 2006), but longer-lasting than corpus persistence in vowel peripherality (Villarreal & Clark, 2022).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In both cases we would characterize the duration of the repetitiveness effect as fairly long-lasting, extending over multiple intervening sentences. Generally speaking, the degree of durability here seems similar to previous results from other morphological and syntactic variables (Gries, 2005; Szmrecsanyi, 2006), but longer-lasting than corpus persistence in vowel peripherality (Villarreal & Clark, 2022).…”
Section: Discussionsupporting
confidence: 90%
“…Lexical repetition can also enhance persistence when the words being repeated contain the variable (as opposed to themselves being embedded in word order alternants). Tamminga (2016) found that persistence in both (ING) variation and coronal stop deletion was stronger in cases where the prime and target were the same word, while Villarreal and Clark (2022) similarly found that persistence in New Zealand English vowel changes was enhanced when prime and target repeated the same lexical item. In the extreme, persistence may be absent (or at least too weak to detect) when potential primes and targets are too dissimilar.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations